Symptoms of depression, anxiety, and somatization in female victims and perpetrators of intimate partner violence in Maputo City, Mozambique - Soares JJ; Macassa G; Zacarias AE; Svanström L; Antai D (Dove Medical Press, 2012)
Antonio Eugenio Zacarias,1,2 Gloria Macassa,3 Joaquim JF Soares,1 Leif Svanström,1 Diddy Antai1,41Karolinska Institutet, Department of Public Health Sciences, Division of Social Medicine, Stockholm, Sweden; 2Eduardo Mondlane University, Faculty of Medicine, Maputo, Mozambique; 3University of Gävle, Department of Occupational and Health Sciences, Gävle, Sweden; 4Division of Global Health and Inequalities, The Angels Trust – Nigeria, Abuja, NigeriaBackground: Little knowledge exists in Mozambique and sub-Saharan Africa about the mental health (symptoms of depression, anxiety, and somatization) of women victims and perpetrators of intimate partner violence (IPV) by type of abuse (psychological aggression, physical assault without/with injury, and sexual coercion). This study scrutinizes factors associated with mental health among women victims and perpetrators of IPV over the 12 months prior to the study.Methods and materials: Mental health data were analyzed with bivariate and multiple regression methods for 1442 women aged 15–49 years who contacted Forensic Services at Maputo Central Hospital (Maputo City, Mozambique) for IPV victimization between April 1, 2007 and March 31, 2008.Results: In bivariate analyses, victims and perpetrators of IPVs scored higher on symptoms of mental health than their unaffected counterparts. Multiple regressions revealed that controlling behaviors, mental health comorbidity, social support, smoking, childhood abuse, sleep difficulties, age, and lack of education were more important in explaining symptoms of mental health than demographics/socioeconomics or life-style factors. Victimization and perpetration across all types of IPV were not associated with symptoms of mental health.Conclusion: In our sample, victimization and perpetration were not important factors in explaining mental ill health, contrary to previous findings. More research into the relationship between women’s IPV victimization and perpetration and mental health is warranted as well as the influence of controlling behaviors on mental health.Keywords: women, depression, anxiety, somatization, victims, perpetrators, controlling behaviors, child abuse, social support